Neonatal Outcomes of Eclamptic Mothers in a Tertiary Government Rural Teaching Hospital of Eastern India: A Prospective, Cross-sectional, Observational, and Epidemiological Study - Santanu Bandyopadhyay; Rajib Das; Medhatithi Burman; Asok Kumar Datta (Research Highlights in Disease and Health Research Vol. 7, 2023)
There are very few studies conducted on the neonatal outcomes of eclamptic women in a rural sociodemographic situation prevailing in India. In view of this, the objective of this study was to identify as well as to assess the importance of neonatal outcomes of eclamptic mothers in a rural community. Thus, a prospective, cross-sectional, observational, and epidemiological study was conducted on two statistically matched groups in a tertiary care government teaching hospital catering rural agro-based population of Eastern India during April 2012–March 2013. One group of study included neonates born to 100 consecutive eclamptic mothers, while the other included neonates delivered to 100 non-eclamptic (control) mothers. The majority of eclamptic mothers were unbooked, primigravidae (86%), in late teens (66%), belonging to socioeconomic Class IV (92%) of modified Kuppuswamy scale (2007). About 72% of neonates were born with one or more adverse neonatal outcomes (p<0.001). Neonatal outcomes as observed in this study were prematurity (40%, p=0.001), low birth weight (LBW) (60%, p<0.001), intrauterine growth restriction (IUGR) (12%, p=0.032), and birth asphyxia (33%, p=0.016), while hypoxic-ischemic encephalopathy, early-onset sepsis, early neonatal death, and stillbirth were not found to be statistically significant. Late preterm births were also significant (p=0.004). This study validates that eclampsia is a significant cause of considerable neonatal morbidity in terms of preterm, LBW, IUGR, and birth asphyxia in the rural population. It is identified as a substantial risk factor for late preterm delivery as well.